Dorsally derived spinal interneurons in locomotor circuits. (26th March 2013) - Vallstedt, Anna; Kullander, Klas
Abstract : During neuronal circuit formation, axons are guided to their targets by the help of axon guidance molecules, which are required for establishing functional circuits. A promising system to dissect the development and functionalities of neuronal circuitry is the spinal cord central pattern generator (CPG) for locomotion, which converts a tonic supraspinal drive to rhythmic and coordinated movements. Here we describe concepts arising from genetic studies of the locomotor network with a focus on the position and roles of commissural interneurons. In particular, this involves studies of several families of axon guidance molecules relevant for midline crossing, the Eph/ephrins and Netrin/DCC. Effects on developing commissural interneurons in mice with aberrant midline axon guidance capabilities suggest that, in addition to ventral populations, dorsal commissural interneurons also play a role in coordinating locomotor circuitry. Recent findings implicate the novel dI6 interneuron marker Dmrt3 in this role. Strikingly, mutations in Dmrt3 result in divergent gait patterns in both mice and horses.